Defining a self-evaluation digital literacy framework for secondary educators: the DigiLit Leicester project - Richard Hall; Lucy Atkins; Josie Fraser (Association for Learning Technology, 2014)
Despite the growing interest in digital literacy within educational policy, guidance for secondary educators in terms of how digital literacy translates into the classroom is lacking. As a result, many teachers feel ill-prepared to support their learners in using technology effectively. The DigiLit Leicester project created an infrastructure for holistic, integrated change, by supporting staff development in the area of digital literacy for secondary school teachers and teaching support staff. The purpose of this article is to demonstrate how the critique of existing digital literacy frameworks enabled a self-evaluation framework for practitioners to be developed. Crucially, this framework enables a co-operative, partnership approach to be taken to pedagogic innovation. Moreover, it enables social and ethical issues to underpin a focus on teacher-agency and radical collegiality inside the domain of digital literacy. Thus, the authors argue that the shared development framework constitutes a new model for implementing digital literacy aimed at transforming the provision of secondary education across a city.